Perubahan dan Pengembangan Organisasi - Latar, Bakroni (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
The purpose of this research is to describe organizational change and development. Library studies are used as methods in this research. Results and discussions show that organizations are objected to by human activities, where humans seek the most benefit from organizational activity through the human beings involved. In the event of such a change, the organization must also undergo development, which is the stage for organizational change.